Risk perception and perceived self-efficacy of deaf and hard-of-hearing seniors and young adults in emergencies - Engelman, Alina; Ivey, Susan L; Tseng, Winston; Neuhauser, Linda (American journal of disaster medicine, 2017)
The authors explored the factors influencing risk perception and perceived self-efficacy before and during an emergency for deaf and hard-of-hearing (Deaf/HH) seniors and young adults. The authors collected demographic survey data and conducted four focus groups with 38 Deaf/HH residents of the San Francisco Bay Area; two groups were with young adults (ages 18-35), including one group of college students and one group of young professionals, and two were with older adults (ages 50-90). Significant differences were found between Deaf/HH young adults and seniors in both the sources of self-efficacy and risk perception and their attitudes toward preparedness. All groups demonstrated high resilience. Deaf/HH young professionals expressed more concern about their risk in an emergency than Deaf/HH college students. Alternately, the risk perception of Deaf/HH older adults was often rooted in their past experiences (survival of past emergencies, inaccessibility of communications during drills). Policy implications include the need to dedicate more resources to increasing accessibility and relevance of emergency communications technology for Deaf/HH populations. This could help increase adaptability before, during, and after emergencies among all groups of Deaf/HH people, particularly among young Deaf/HH professionals.